INTEGRAÇÃO TEORIA-PRÁTICA NO CUIDADO HUMANIZADO: VIVÊNCIAS DE ACADÊMICOS DE ENFERMAGEM EM EXTENSÃO ILPI (CIPEEX, 2026)
Introduction: This experience report addresses the integration between theory and practice in humanized care, based on the experience of Nursing students in a Long-Term Care Institution for the Elderly (LTCI). Objective: To describe the students’ experience with extension activities grounded in Jean Watson’s Theory of Human Care and modern psychological theories, highlighting their impact on the well-being of older adults.  Method: This is a descriptive, qualitative experience report of an extension activity linked to the Health Psychology course, carried out at the LTCI. Activities included bingo (radical behaviorism), music therapy (cognitive theory), and active listening (Watson), respecting the physical, emotional, social, cultural, and spiritual aspects of the elderly. Results: Enthusiasm, memory recall, strengthening of bonds, and promotion of participants’ overall well-being were observed. Conclusion: The experience brought health benefits to the elderly and contributed to the critical and humanized education of the students, underscoring the importance of integrating teaching, research, and extension in Nursing education. Continuation and evaluation of these activities are recommended.Keywords: Holistic Care; Elderly; Nursing Theories; Nursing.
Keywords: Cuidado Holístico; Idosos; Teorias de Enfermagem; Enfermagem